2018
DOI: 10.1111/jvp.12486
|View full text |Cite
|
Sign up to set email alerts
|

The impact ofMK‐467 on plasma drug concentrations, sedation and cardiopulmonary changes in sheep treated with intramuscular medetomidine and atipamezole for reversal

Abstract: The effect of MK‐467, a peripheral α2‐adrenoceptor antagonist, on plasma drug concentrations, sedation and cardiopulmonary changes induced by intramuscular (IM) medetomidine was investigated in eight sheep. Additionally, the interactions with atipamezole (ATI) used for reversal were also evaluated. Each animal was treated four times in a randomized prospective crossover design with 2‐week washout periods. Medetomidine (MED) 30 μg/kg alone or combined in the same syringe with MK‐467 300 μg/kg (MMK) was injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Concentrations of dexmedetomidine in canine plasma were determined with chiral high-performance liquid chromatographyemass spectrometry (HPLCeMS/MS, Sciex API 4000; AB Sciex Pte. Ltd, ON, Canada) as described previously (Adam et al 2018). Reference samples were prepared in drug-free canine plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of dexmedetomidine in canine plasma were determined with chiral high-performance liquid chromatographyemass spectrometry (HPLCeMS/MS, Sciex API 4000; AB Sciex Pte. Ltd, ON, Canada) as described previously (Adam et al 2018). Reference samples were prepared in drug-free canine plasma.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, renewed interest in its potential to prevent the peripheral, while preserving the central effects of α 2 -adrenoceptor agonists, has been the subject of numerous studies investigating cardiopulmonary, sedative and metabolic outcomes in several species. In brief, vatinoxan has been shown to either attenuate or prevent the cardiovascular effects of various α 2 -adrenoceptor agonists in dogs (Pagel et al 1998;Enouri et al 2008;Honkavaara et al 2008Honkavaara et al , 2011Rolfe et al 2012), horses (Bryant et al 1998;de Vries et al 2016;Tapio et al 2018), sheep (Bryant et al 1998;Raekallio et al 2010: Adam et al 2018) and cats (Pypendop et al 2017a;Siao et al 2017). Moreover, its impact on agonistinduced sedation appears to be minor and more related to alteration on the disposition of coadministered agonists drugs through attenuation of their cardiovascular effects (Vainionpaa et al 2013;Bennett et al 2016;Restitutti et al 2017;Adam et al 2018;Pypendop et al 2016Pypendop et al , 2017bHonkavaara et al 2017a, b).…”
Section: Introductionmentioning
confidence: 99%
“…39 Studies in sheep and dogs showed lower haemoglobin concentrations when the alpha-2-adrenergic agonist was combined with VTX. 12,13,41 All animals showed a sufficient level plane of anaesthesia, and no difference was detected between treatments. However, the additional anaesthetic effects of tiletamine and zolazepam used in the study does not allow interpretation of the impact of VTX on the level or duration of the medetomidine-induced sedation.…”
Section: Discussionmentioning
confidence: 86%